Morphology dependent interaction between Co(ii)-tetraphenylporphyrin and the MgO(100) surface - Ninova, Silviya; Malcıoğlu, Osman Barış; Auburger, Philipp; Franke, Matthias; Lytken, Ole; Steinrück, Hans-Peter; Bockstedte, Michel (Physical Chemistry Chemical Physics, 2021)
Porphyrins are key elements in organic-inorganic hybrid systems for a wide range of applications. Understanding their interaction with the substrate gives a handle on structural and electronic device properties. Here we investigate a single transition-metal porphyrin, namely Co(ii)-tetraphenylporphyrin (CoTPP), on the MgO(100) surface and the effect of multilayer film formation within hybrid density-functional theory and many-body perturbation theory. We focus on the relevant adsorption sites, simulate their photoemission spectra as a key fingerprint and compare with experiments on MgO(100) films on Ag(100). While we find only weak interaction between the cobalt centre and terrace sites on the MgO(100) surface, a strong interaction manifests itself with the low-coordinated sites. This leads to distinct features in both the valence and core-level regions of the electronic structure, as observed in the ultraviolet and X-ray photoemission spectra, corroborated by simulated spectra and calculated cobalt core-level shifts. Our work thus demonstrates the relevance of morphology-related low-coordinated sites and their properties in the adsorption of CoTPP on the MgO(100) surface.
CRIS-Team Scopus Importer:2021-02-12